Partial purification and identification of antibacterial peptides from the endophytic fungus KT31 isolated from Kappaphycus alvarezii: Purifikasi parsial dan identifikasi peptida antibakteri dari kapang endofit KT31 yang diisolasi dari makroalga Kappaphycus alvarezi - Sofyana, Neng Tanty; Mustopa, Apon Zaenal; Iriani Setyaningsih; Tarman, Kustiariyah; Maulidiani, Maulidiani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Endophytic fungi produce a wide array of secondary metabolites with diverse biological activities, including antibacterial, antifungal, insecticidal, and immunosuppressive effects. The increasing prevalence of infections caused by pathogenic bacteria, such as Escherichia coli, Bacillus subtilis, Salmonella typhi, Pseudomonas aeruginosa, Listeria monocytogenes, Bacillus pumilus, and Staphylococcus aureus, highlights the urgent need for novel antibacterial agents. This study aimed to determine the optimal concentration of ammonium sulfate for the isolation of endophytic fungus KT31 from Kappaphycus alvarezii based on its antibacterial activity. Fungal proteins were extracted using ammonium sulfate precipitation at varying saturation levels and subsequently tested for antibacterial activity against a panel of seven pathogenic bacterial strains. Crude protein extracts demonstrating promising activity were further purified using gel filtration chromatography with Sephadex G-50, followed by molecular weight determination usingDS-PAGE and protein quantification using a Bicinchoninic Acid (BCA) assay. The highest antibacterial activity was observed in the protein fraction precipitated at 80% ammonium sulfate saturation, exhibiting inhibition zones of up to 14 mm against E. coli and B. pumilus. A notable inhibition zone of 12 mm was observed for the most active chromatographic fraction. SDS-PAGE analysis revealed that the active protein had an estimated molecular weight of 11.27 kDa. These findings suggest that endophytic fungi, particularly the isolate KT31, represent a promising source of novel antibacterial peptides, warranting further investigation for therapeutic applications.